Hospital Efficiency in Indonesia with Frontier Analysis - Abdurachman, Edi; Eni, Yuli; Furinto, Asnan; Warganegara, Dezie; Gautama So, Idris (KnE Social Sciences, 2019)
Hospitals are health care institutions for people who provide individual health services. Health services in hospitals are provided for inpatients, outpatients, and emergency unit patient. Facilities in the hospital are also provided for the fulfillment of health services for all patients. However, currently, there are still many doctors who are unbalanced in getting patients. For example, in a hospital, there is a doctor who is a favorite of patients, so they have a large queue of patients. However, on the other hand, some doctors are not favorites so that almost no patients come. This makes the hospital inefficient in terms of labor and time. This study discusses the efficiency of existing resources in hospitals which includes input variables (beds, general practitioners, specialist doctors, nurses, pharmacists, medical technicians, health workers, non-health workers, building area) and output variables (inpatient, outpatient, and patient emergency unit). The method used in this study is Stochastic Frontier Analysis using Frontier 4.1 software. The results indicated that more than 50% of the hospitals are below the efficiency average. This happens for the three types of output. Keywords: efficiency, frontier, inpatient, outpatient, emergency unit patient